Hubungan antara ekspresi BRAF V600E dengan metastasis dan derajat diferensiasi pada adenokarsinoma kolorektal - Ni Kadek Ayu Maya Damayanti; Ni Wayan Winarti; Ni Putu Sriwidyani; Luh Putu Iin Indrayani Maker; Herman Saputra; I Made Muliarta (Intisari Sains Medis, 2021)
Background: Colorectal carcinoma is a malignant epithelial tumor of the large bowel that occurs due to extrinsic and intrinsic factors. BRAF V600E gene mutation was found in about 10-15% of colorectal carcinoma. This mutation was associated with aggressive biologic behaviors, metastasis and lesser responsiveness to EGFR inhibitors therapy. This study aims to determine the association between BRAF V600E expression with metastasis and the degree of differentiation of colorectal adenocarcinoma.Methods: This cross sectional study involved 43 samples of adenocarcinoma colorectal patients who had histopathological examinations in the period 2018-2019. Immunohistochemical were performed to assess the expression of BRAF V600E. This expression was concluded positively if 75% or more tumor cells showed intense cytoplasmic staining. Data were analyzed using SPSS version 20 for Windows.Results: Within 43 colorectal adenocarcinoma cases, it was found 7 cases (16.3%) had a positive expression of BRAF V600E. This expression was found in metastasis cases (7/25), not found in cases without metastasis (0/18). There was an association between BRAF V600E expression and metastasis (p=0.014). The positive expressions of BRAF V600E were only found in low-grade differentiation (7/35 cases), were not found in high-grade differentiation (0/8 cases), and no association between BRAF V600E mutation and the degree of differentiation (p=0.167).Conclusion: There was an association between BRAF V600E expression and metastasis of colorectal adenocarcinoma. There was no significant association between BRAF V600E expression and the degree of differentiation of colorectal adenocarcinoma. Latar Belakang: Karsinoma kolorektal merupakan suatu tumor ganas epitelial usus besar yang terjadi akibat pengaruh dari faktor ekstrinsik dan intrinsik. Mutasi gen BRAF V600E ditemukan pada sekitar 10-15% kasus karsinoma kolorektal. Mutasi ini berkaitan dengan perilaku biologik agresif, metastasis, serta kurangnya respon terhadap terapi dengan inhibitor EGFR. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara ekspresi BRAF V600E dengan metastasis dan derajat diferensiasi adenokarsinoma kolorektal.Metode: Penelitian menggunakan rancangan analitik potong lintang dengan 43 sampel penderita adenokarsinoma kolorektal yang telah dilakukan pemeriksaan histopatologi pada periode tahun 2018-2019. Pulasan imunohistokimia dikerjakan untuk menilai ekspresi BRAF V600E. Ekspresi BRAF V600E dinyatakan positif jika 75% atau lebih sel tumor mununjukkan pulasan sitoplasma dengan intensitas kuat. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Dari 43 kasus, ditemukan 7 kasus (16,3%) dengan ekspresi BRAF V600E positif. Ekspresi ini hanya dijumpai pada kasus dengan metastasis (7 dari 25 kasus), tidak dijumpai pada kasus tanpa metastasis (0 dari 18 kasus). Didapatkan hubungan bermakna antara ekspresi BRAF V600E dengan metastasis (p=0,014). Ekspresi BRAF V600E positif hanya ditemukan pada kasus derajat diferensiasi rendah (7 dari 35 kasus), tidak ditemukan pada derajat tinggi (0 dari 8 kasus), dan hubungan tersebut tidak bermakna secara statistik (p=0,167).Kesimpulan: Terdapat hubungan antara ekspresi BRAF V600E dengan metastasis pada adenokarsinoma kolorektal. Tidak terdapat hubungan antara ekspresi BRAF V600E dengan derajat diferensiasi pada adenokarsinoma kolorektal.